PENGARUH MODAL MANUSIA DAN PEMBELAJARAN ORGANISASI TERHADAP KINERJA ORGANISASI YANG DIMEDIASI KOMPETENSI ORGANISASI DAN BUDAYA INOVASI (Studi Pada Perguruan Tinggi Swasta Di Kopertis Wilayah V Daerah Istimewa Yogyakarta) - WINARNO ; Prof. Dr. Eka Afnan Troena, SE Prof. Armanu, SE., M.Sc., Ph.D Dr. Ir. Solimun, MS
The purpose of this research was to examine and analyze: The Influences of_x000D_ Human Capital and Organizational Learning on Organizational Performance_x000D_ Mediated by Organizational Competence and Innovation Culture. _x000D_ The object and sample of this study were the Private Higher Education_x000D_ Institutions in Kopertis V Yogyakarta. This study used a survey approach with cross_x000D_ sectional design. The technique for collecting the samples was total sampling or_x000D_ census. The respondents in this study were the Private Higher Education Institutions_x000D_ having at least 50% accredited study programs. The testing model was Structural_x000D_ Equation Modeling (SEM) using Partial Least Square (PLS) method. _x000D_ The results show that: (1) Intellectual capital is the most important indicator of_x000D_ human capital in increasing organizational performance that is reflected in the_x000D_ improvement of learning system, (2) Personal skills are the most important indicators_x000D_ of organizational learning in improving organizational performance as reflected by_x000D_ the improvement in the learning system, (3) The quality of education and teaching is_x000D_ the most important indicator of the organizational competence in improving_x000D_ organizational performance which is reflected by the learning system improvement